Vitamin D deficiency is Associated with Increased Risk of Delirium and Mortality among Critically Ill, Elderly Covid-19 Patients - Zahra Gholi; Davood Yadegarynia; Hassan Eini-Zinab; Zahra Vahdat Shariatpanahi (Elsevier, 2022)
Background and aim: Data on the associations of vitamin D levels with severe outcomes of coronavirus disease 2019 (COVID-19) among critically ill elderly patients are not conclusive and also no information is available about some outcomes such as delirium. Therefore, the current study was done to assess these associations in critically ill elderly COVID-19 patients. Methods: In total, 310 critically ill COVID-19 patients, aged ≥ 65 years, were included in the current single center prospective study. All patients were hospitalized in the intensive care unit (ICU). We collected data on demographic characteristics, laboratory parameters, blood pressure, comorbidities, medications, and types of mechanical ventilation at baseline (the first day of ICU admission). Patients were categorized based on serum 25(OH)D3 levels at the baseline [normal levels (>30 ng/mL), insufficiency (20-30 ng/mL), deficiency (<20 ng/mL)]. Data on delirium incidence, mortality, invasive mechanical ventilation (IMV) requirement during treatment, length of ICU and hospital admission, and re-hospitalization were recorded until 45 days after the baseline. Results: Vitamin D deficiency and insufficiency were prevalent among 12 % and 37 % of study participants, respectively. In terms of baseline differences, patients with vitamin D deficiency were more likely to be older, have organ failure, take propofol, need IMV, and were less likely to need face mask compared to patients with normal levels of vitamin D. A significant positive association was found between vitamin D deficiency and risk of delirium. After controlling for potential confounders, patients with vitamin D deficiency had a 54 % higher risk of delirium compared to those with vitamin D sufficiency (HR: 1.54, 95 % CI: 1.02-2.33). Such a positive association was also seen for 45-day COVID-19 mortality (HR: 3.95, 95 % CI: 1.80-8.67). Also, each 10 ng/mL increase in vitamin D levels was associated with a 45 % and 26 % lower risk of 45-day mortality (HR: 0.55, 95 % CI: 0.40-0.74) and ICU mortality due to COVID-19 (HR: 0.74, 95 % CI: 0.60-0.92), respectively. In terms of other COVID-19 outcomes including IMV requirement during treatment, prolonged hospitalization, and re-hospitalization, we found no significant association in relation to serum 25(OH)D3 levels either in crude or fully adjusted models. Conclusion: Vitamin D deficiency was associated with an increased risk of delirium and mortality among critically ill elderly COVID-19 patients.